EFEKTIVITAS PEMBERIAN MEDIA TANAM DAN POC CANGKANG TELUR DALAM PENINGKATAN KESUBURAN TANAH PADA STEK TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Monica, Cici; Tarigan, Ruth Riah Ate; Lubis, Najla (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this research was to determine the effectiveness of providing planting media and eggshell poc in increasing soil fertility on grape plant (vitis vinifera) cuttings in the pre-nursery and their interactions. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the study. The first factor examined was the treatment of planting media with the symbol